Tolerance mechanisms in polysaccharide biosynthesis: Implications for undecaprenol phosphate recycling in Escherichia coli and Shigella flexneri. - Jilong Qin; Yaoqin Hong; Nicholas T Maczuga; Renato Morona; Makrina Totsika (PLoS Genetics)
Bacterial polysaccharide synthesis is catalysed on the universal lipid carrier, undecaprenol phosphate (UndP). The cellular UndP pool is shared by different polysaccharide synthesis pathways including peptidoglycan biogenesis. Disruptions in cytosolic polysaccharide synthesis steps are detrimental to bacterial survival due to effects on UndP recycling. In contrast, bacteria can survive disruptions in the periplasmic steps, suggesting a tolerance mechanism to mitigate UndP sequestration. Here we investigated tolerance mechanisms to disruptions of polymerases that are involved in UndP-releasing steps in two related polysaccharide synthesis pathways: that for enterobacterial common antigen (ECA) and that for O antigen (OAg), in Escherichia coli and Shigella flexneri. Our study reveals that polysaccharide polymerisation is crucial for efficient UndP recycling. In E. coli K-12, cell survival upon disruptions in OAg polymerase is dependent on a functional ECA synthesis pathway and vice versa. This is because disruptions in OAg synthesis lead to the redirection of the shared lipid-linked sugar substrate UndPP-GlcNAc towards increased ECA production. Conversely, in S. flexneri, the OAg polymerase is essential due to its limited ECA production, which inadequately redirects UndP flow to support cell survival. We propose a model whereby sharing the initial sugar intermediate UndPP-GlcNAc between the ECA and OAg synthesis pathways allows UndP to be redirected towards ECA production, mitigating sequestration issues caused by disruptions in the OAg pathway. These findings suggest an evolutionary buffering mechanism that enhances bacterial survival when UndP sequestration occurs due to stalled polysaccharide biosynthesis, which may allow polysaccharide diversity in the species to increase over time.